Abnormal transport behaviors in traveling wave system. (September 2019) - Chen, Ruyin; Wang, Chaojie; He, Zhifen
Abstract: In general, for a traveling wave system, a particle always follows the wave with wave velocity or moves in the same direction but with a lower velocity. Here, we investigate transport of an inertial particle in a deterministic traveling wave system subjected to a symmetric periodic signal. Our numerical results indicate that only with the help of the signal, can the particle move against the direction of propagation of the traveling wave, forming an absolutely opposite motion. Without external bias, direction of its mean velocity changes several times with the traveling wave velocity and angular frequency of the signal, i.e., a multiple current reversal phenomenon. In the presence of the external bias, the system experiences nonlinear negative mobility. The intrinsic physical mechanisms and conditions responsible for the occurrence of the anomalous transport phenomena are analyzed in detail.